Welcome to Westonci.ca, the place where your questions find answers from a community of knowledgeable experts. Discover a wealth of knowledge from experts across different disciplines on our comprehensive Q&A platform. Our platform provides a seamless experience for finding reliable answers from a network of experienced professionals.
Sagot :
Certainly! Let's find the corresponding [tex]\( y \)[/tex] values for the given [tex]\( x \)[/tex] values using the linear equation [tex]\( y = -6x - 3 \)[/tex].
Given the table:
[tex]\[ \begin{array}{|c|c|} \hline x & y \\ \hline -5 & \square \\ \hline -1 & \square \\ \hline 0 & \square \\ \hline 1 & \square \\ \hline \end{array} \][/tex]
### Step-by-Step Solution
1. For [tex]\( x = -5 \)[/tex]:
Substitute [tex]\( x = -5 \)[/tex] into the equation [tex]\( y = -6x - 3 \)[/tex]:
[tex]\[ y = -6(-5) - 3 \][/tex]
Simplify inside the parentheses:
[tex]\[ y = 30 - 3 \][/tex]
Finally, subtract 3:
[tex]\[ y = 27 \][/tex]
2. For [tex]\( x = -1 \)[/tex]:
Substitute [tex]\( x = -1 \)[/tex] into the equation [tex]\( y = -6x - 3 \)[/tex]:
[tex]\[ y = -6(-1) - 3 \][/tex]
Simplify inside the parentheses:
[tex]\[ y = 6 - 3 \][/tex]
Finally, subtract 3:
[tex]\[ y = 3 \][/tex]
3. For [tex]\( x = 0 \)[/tex]:
Substitute [tex]\( x = 0 \)[/tex] into the equation [tex]\( y = -6x - 3 \)[/tex]:
[tex]\[ y = -6(0) - 3 \][/tex]
Multiply by zero and subtract 3:
[tex]\[ y = -3 \][/tex]
4. For [tex]\( x = 1 \)[/tex]:
Substitute [tex]\( x = 1 \)[/tex] into the equation [tex]\( y = -6x - 3 \)[/tex]:
[tex]\[ y = -6(1) - 3 \][/tex]
Simplify inside the parentheses:
[tex]\[ y = -6 - 3 \][/tex]
Finally, add the negative numbers:
[tex]\[ y = -9 \][/tex]
Now, we can fill in the table with the calculated values:
[tex]\[ \begin{array}{|c|c|} \hline x & y \\ \hline -5 & 27 \\ \hline -1 & 3 \\ \hline 0 & -3 \\ \hline 1 & -9 \\ \hline \end{array} \][/tex]
Given the table:
[tex]\[ \begin{array}{|c|c|} \hline x & y \\ \hline -5 & \square \\ \hline -1 & \square \\ \hline 0 & \square \\ \hline 1 & \square \\ \hline \end{array} \][/tex]
### Step-by-Step Solution
1. For [tex]\( x = -5 \)[/tex]:
Substitute [tex]\( x = -5 \)[/tex] into the equation [tex]\( y = -6x - 3 \)[/tex]:
[tex]\[ y = -6(-5) - 3 \][/tex]
Simplify inside the parentheses:
[tex]\[ y = 30 - 3 \][/tex]
Finally, subtract 3:
[tex]\[ y = 27 \][/tex]
2. For [tex]\( x = -1 \)[/tex]:
Substitute [tex]\( x = -1 \)[/tex] into the equation [tex]\( y = -6x - 3 \)[/tex]:
[tex]\[ y = -6(-1) - 3 \][/tex]
Simplify inside the parentheses:
[tex]\[ y = 6 - 3 \][/tex]
Finally, subtract 3:
[tex]\[ y = 3 \][/tex]
3. For [tex]\( x = 0 \)[/tex]:
Substitute [tex]\( x = 0 \)[/tex] into the equation [tex]\( y = -6x - 3 \)[/tex]:
[tex]\[ y = -6(0) - 3 \][/tex]
Multiply by zero and subtract 3:
[tex]\[ y = -3 \][/tex]
4. For [tex]\( x = 1 \)[/tex]:
Substitute [tex]\( x = 1 \)[/tex] into the equation [tex]\( y = -6x - 3 \)[/tex]:
[tex]\[ y = -6(1) - 3 \][/tex]
Simplify inside the parentheses:
[tex]\[ y = -6 - 3 \][/tex]
Finally, add the negative numbers:
[tex]\[ y = -9 \][/tex]
Now, we can fill in the table with the calculated values:
[tex]\[ \begin{array}{|c|c|} \hline x & y \\ \hline -5 & 27 \\ \hline -1 & 3 \\ \hline 0 & -3 \\ \hline 1 & -9 \\ \hline \end{array} \][/tex]
Your visit means a lot to us. Don't hesitate to return for more reliable answers to any questions you may have. We appreciate your visit. Our platform is always here to offer accurate and reliable answers. Return anytime. Westonci.ca is your trusted source for answers. Visit us again to find more information on diverse topics.